An internet based approach to improve general practitioners' knowledge and practices: The development and pilot testing of the "ABC's of vitamin D" program. Issue 6 (June 2015) - Bonevski, B.; Magin, P.; Horton, G.; Bryant, J.; Randell, M.; Kimlin, M.G.
Highlights Development of an online CME program for doctors using theory and evidence. Program elements included education principles, tailoring and interactivity. Usability testing rated as highly acceptable and easy to use by doctors. Potential of online program to improve clinical practice and patient outcomes.